Current advances in transfusion medicine: a 2019 review of selected topics from the AABB Clinical Transfusion Medicine Committee. Issue 7 (29th May 2020) - Pagano, Monica B.; Allen, Elizabeth S.; Chou, Stella T.; Dunbar, Nancy M.; Gniadek, Thomas; Goel, Ruchika; Harm, Sarah K.; Hopkins, Courtney K.; Jacobson, Jessica; Lokhandwala, Parvez M.; Metcalf, Ryan A.; Raval, Jay S.; et al.
Abstract : BACKGROUND: The AABB Clinical Transfusion Medicine Committee (CTMC) compiles an annual synopsis of the published literature covering important developments in the field of transfusion medicine (TM) for the board of director's review. This synopsis is now made available as a manuscript published in TRANSFUSION. STUDY DESIGN AND METHODS: CTMC committee members review original manuscripts including TM‐related topics published in different journals between late 2018 and 2019. The selection of topics and manuscripts are discussed at committee meetings and are chosen based on relevance and originality. After the topics and manuscripts are selected, committee members work in pairs to create a synopsis of the topics, which is then reviewed by two committee members. The first and senior authors of this manuscript assembled the final manuscript. Although this synopsis is comprehensive, it is not exhaustive, and some papers may have been excluded or missed. RESULTS: The following topics are included: infectious risks to the blood supply, iron donor studies, pre‐transfusion testing interference and genotyping, cold agglutinin disease (CAD), HLA alloimmunization in platelet transfusions, patient blood management, updates to TACO and TRALI definitions, pediatric TM, and advances in apheresis medicine. CONCLUSION: This synopsis provides easy access to relevant topics and may be useful as an educational tool.